2023
DOI: 10.1161/circimaging.122.014106
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Cardiovascular Magnetic Resonance Imaging for Resumption of Athletic Activities Following COVID-19 Infection: An Expert Consensus Document on Behalf of the American Heart Association Council on Cardiovascular Radiology and Intervention Leadership and Endorsed by the Society for Cardiovascular Magnetic Resonance

Abstract: The global pandemic of COVID-19 caused by infection with SARS-CoV-2 is now entering its fourth year with little evidence of abatement. As of December 2022, the World Health Organization Coronavirus (COVID-19) Dashboard reported 643 million cumulative confirmed cases of COVID-19 worldwide and 98 million in the United States alone as the country with the highest number of cases. Although pneumonia with lung injury has been the manifestation of COVID-19 principally responsible for morbidity and mortality, myocard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
(296 reference statements)
0
3
0
1
Order By: Relevance
“…A COVID-19 é uma doença que pode ser apresentada de várias formas a depender da gravidade da doença, a infecção pelo SARS-CoV-2 pode manifestar como assintomática ou pré-sintomática, quando não há nenhum sintoma da doença, no entanto, o teste virológico é positivado; doença leve quando a patologia afeta a via respiratória superior e há alguns sintomas leves sem apresentação da falta de ar ou a imagem anormal do tórax; doença moderada tem repercussão no trato respiratória inferior na avaliação clínica ou de imagem, além de alteração da saturação (SpO 2 ≥ 94%); na doença grave a saturação é reduzida consideravelmente (SpO 2 <94%, PaO 2 /FiO 2<300 mm Hg), além do aumento da frequência respiratória (>30 respirações/min ou infiltrados pulmonares >50%); e a manifestação crítica é quando há insuficiência respiratória, choque séptico ou disfunção de múltiplos órgãos ( RUBERG et al, 2023).…”
Section: Resultsunclassified
“…A COVID-19 é uma doença que pode ser apresentada de várias formas a depender da gravidade da doença, a infecção pelo SARS-CoV-2 pode manifestar como assintomática ou pré-sintomática, quando não há nenhum sintoma da doença, no entanto, o teste virológico é positivado; doença leve quando a patologia afeta a via respiratória superior e há alguns sintomas leves sem apresentação da falta de ar ou a imagem anormal do tórax; doença moderada tem repercussão no trato respiratória inferior na avaliação clínica ou de imagem, além de alteração da saturação (SpO 2 ≥ 94%); na doença grave a saturação é reduzida consideravelmente (SpO 2 <94%, PaO 2 /FiO 2<300 mm Hg), além do aumento da frequência respiratória (>30 respirações/min ou infiltrados pulmonares >50%); e a manifestação crítica é quando há insuficiência respiratória, choque séptico ou disfunção de múltiplos órgãos ( RUBERG et al, 2023).…”
Section: Resultsunclassified
“…Consensus statements suggest the use of CMR for athletes post COVID-19 infection with abnormal initial screening [ 5 , 31 ]. Our systematic review and meta-analysis provides a scientific rationale for the current guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…With the spread of the COVID-19 pandemic, concerns have been raised as to whether athletes would be at increased risk of myocardial involvement and subsequent adverse events. CMR is the gold standard technique that allows in-depth assessment of the myocardium and the diagnosis of pathological fibrosis and oedema [ 5 ]. Along with clinical evaluation and physical examination, CMR has an important role in the assessment of athletes before they return to intensive training and competitions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac magnetic resonance (CMR) has the unique capability of characterising myocardial tissue properties in vivo , including evaluation for myocardial oedema. Numerous studies have reported CMR abnormalities in patients who recovered from COVID-19 infection ( 9 , 16 , 26 , 27 ). A case report was published in the early period of the pandemic presenting an interesting association between elevated biomarkers of myocardial injury with generalised myocardial oedema without late gadolinium enhancement in CMR and normal echocardiogram during COVID-19 ( 26 ).…”
Section: Discussionmentioning
confidence: 99%